THE PROCESS OF INTEGRATION INTO THE INTERNATIONAL FINANCIAL MARKETS IN THE DEVELOPMENT OF THE FUND MARKET IN UZBEKISTAN - Makhmudov Samariddin Bakhriddinovich; Jomurodov Khasan (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article assesses the effects of Uzbekistan's stock market's growth and integration into global financial markets. In addition, integration into global financial markets, drawing in foreign capital, promoting economic growth, and boosting stock market efficiency and liquidity are all important factors in the current financial systems' configuration